Akurasi dalam Mengidentifikasi Talenta Siswa Lanjutan Menggunakan Metode Multifactor Evaluation Process (MFEP) - Riski Randa Hidayatullah; Sumijan Sumijan; Yuhandri Yunus (Jurnal Informasi dan Teknologi, 2020)
Talent is a natural ability to acquire knowledge and skills, both general and specific. Basically, each individual has different talents. moreover supported by the appropriate talents, will bring passion and give pleasure in learning or living it. Providing an overview to students of who they are through their talents and interests so that what job opportunities they can initiate after graduating from school are qualitative data related to the research focus, namely the process of identifying student talents in the Educator Room of SMAN 1 Linggo Sari Baganti . There are at least nine intelligences or talents that a person may possess, namely logical mathematical, linguistic / verbal, visual spatial, musical, bodily-kinesthetic, interpersonal, intrapersonal, natural, and moral / spiritual. Sources of data in the study were obtained from primary data, namely data obtained directly from data sources, namely the people involved in the process of identifying talents in the Educator Room of SMAN 1 Linggo Sari Baganti. In addition, the data source in this study is in the form of secondary sources, for example in the form of documents related to curriculum implementation. Furthermore, the data is processed using the Multifactor Evaluation Process (MFEP) method. MFEP is a quantitative method that uses a 'weighting system' and this study uses the VB.NET 2017 language program and MySQL. The processing stages are determining criteria, calculations and processes so as to produce decisions. The sum above results, there are 10 students whose data is processed and produces a total calculation or accuracy of 86.51%. So that this research can be a reference in making the right decision at SMAN 1 Linggo Sari Baganti School.